A CASE REPORT ON GUGGULU BASED KSHARSUTRA ALONG WITH SAPTAVINSHATI GUGGULU IN TREATMENT OF BHAGANDARA (FISTULA-IN-ANO) - Suman Yadav; Ashutosh Kumar Yadav; Anand puri (AYUSHDHARA, 2020)
Bhagandara is one of the commonest diseases which occur in anorectal region. Acharya Sushruta had described this disease in Ashtamahagada that means disease difficult to cure. It starts as deep rooted Pidika around the Guda within two Angula or finger circumference and form into a track with an external opening in the skin of perianal region and an internal opening in the mucosa of anal canal or rectum lined by unhealthy granulation tissue and fibrous tissue which in modern science can be correlated to Fistula-in-ano. As the recurrence rate of fistula in ano is high after modern treatment. To overcome these difficulties, the concept of Ksharsutra mentioned in the classics is very beneficial from the treatment point of view. So, the Guggulu (Commiphora mukul) based Ksharsutra therapy along with oral Ayurvedic formulations is taken to prove its efficacy in treating Bhagandara. Here a case report of a 32 year old, male patient having history of Bhagandara (Fistula-in-ano) since last 2 years is discussed. He had complaints of left gluteal swelling, pain, pus discharge from perianal region and itching around anal region. For which he took allopathic treatment and got no relief, finally patient came to our hospital for better Ayurvedic management. He was treated with Guggulu based Ksharsutra therapy along with oral medication of Saptavinshati Gugglu vati 500 mg with water twice daily. Lastly, he got treated in 60 days and follow up of the patient was maintained up to 6 months where no complication was reported. It was proved that Ksharsutra application in combination with oral Ayurvedic medication worked effectively. This case report will help and enlighten the budding young scholars working in this area.